Efficacy of Modified Eggs and Chick Muscles on Oxidative Stress of Type-2 Diabetes Mellitus Induced Male Wistar Rats - Singh, Kshetrimayum Birla; Taneja, Satish Kumar (Journal of Nutritional Therapeutics, 2013)
A modified poultry egg (Indian Patent Application No. 2264/Del-2005) and chick muscle enriched with optimum minerals, vitamin E and omega-3 fatty acid were developed and its efficacy was studied on oxidative stress of Type-2 diabetes mellitus induced male wistar rats. In this study, two groups of rats were fed on semi-synthetic diet containing 20 mg Zn/kg (control, group-I) and 80 mg Zn/kg (group-II) diet respectively for a period of 6 months. The study revealed that the gain in body weight increased in rats in Zn concentration dependent manner. The urine examined on weekly basis showed glucosuria in group-II on week 8 and thereafter. The blood lipid profile displayed a significant rise in serum glucose, total lipids, cholesterol, triglycerides, LDL-cholesterol, VLDL-cholesterol whereas HDL-cholesterol showed a reduction in their levels in group-II rats than their control counter parts. They displayed higher lipid peroxidation products and activities of superoxide dismutase, catalase, glutathione–s -transferase, glutathione reductase, glutathione (reduced) and glucose-6-phosphate dehydrogenase were significantly lowered and revealed a higher Zn concentration and lower Cu, Mg and Mn both in liver and kidney. On day 90, the male rats in group-II after the establishment of type-2 diabetes mellitus, were divided in to two groups- group-IIA and group-IIB. Feeding on these eggs and chick muscles mixed diet in these groups of rats, all the abnormalities were restored and a considerable reduction in lipid peroxidation products and a significant increased in the activities of enzymes per se with reversal of Zn, Cu, Mg and Mn levels closer to the control group were recorded. The present data suggest that these modified egg and chick muscle are effective in ameliorating the oxidative stress in type-2 diabetes mellitus induced male rats.